THE 'ILLAT APPROACH IN ANALYZING THE HADITH ABOUT ISBAL: A STUDY OF THE PROHIBITION - Nada Ramadhania; Pakhurrozi; Rafil Abil Alfarisi; Syamsudin Hasibuan; Laila Sari Mansyur (International Journal of Multidisciplinary Reseach, 2025)
This study discusses the application of the science of 'illat al-hadith in understanding and analyzing the traditions about the prohibition of isbal, which is extending clothes beyond the ankles. Isbal is a fiqh issue that causes differences in views among scholars, so it requires in-depth study of the historical aspects and context of Islamic law. This research uses a qualitative approach with a literature study method, examining the traditions that mention the prohibition of isbal absolutely and those that relate it to the intention of arrogance (Kibr). The results show two approaches in understanding the prohibition of isbal. First, the absolute prohibition that applies regardless of the intention of the perpetrator. Second, the conditional prohibition that makes the element of pride as illat or cause of the law. This 'illat approach emphasizes the moral purpose of sharia, which is to avoid arrogance, not only assessing external aspects such as the length of clothing. Thus, this approach provides an understanding that is more contextual and relevant to the conditions of modern society. It opens up space for a more flexible interpretation of the law, while still maintaining the basic principles of Islamic sharia. This approach emphasizes the importance of understanding the essence of the law, not just the external form of behavior.